Synthesis of phenylazonaphtol-β-D-O-glycosides, evaluation as substrates for beta-glycosidase activity and molecular studies - Brito-Arias, Marco (Springer, 2014)
BACKGROUND: Phenylazonaphtol-β-D-O-glycosides are alternative substrates for the detection of enzymatic activity of β-glycosidases which are involved in various important processes. These azoic compounds are currently exploited as prodrugs for colonic disease due the presence of β-glycosidase activity in the gut flora and therefore allowing the release of the drug at the specific site. RESULTS: Phenylazonaphtol-β-D-O-glucoside 3a and galactoside 3b were prepared via diazonium salt conditions under weak acidic conditions which do not compromise the O-glycosidic bond stability, by coupling reaction between 2-naphtol sodium salt with aminoglycosides 1a and 1b. The resulting phenylazonaphtol glycosides 2a and 2b were deprotected affording the phenylazonaphtol glycosides 3a and 3b in quantitative yield. The galactoside glycoside 3b was assayed as substrate for in vitro β-galactosidase enzymatic activity showing strong absorbance after releasing of the azoic chromophore. Also, docking studies were performed to determine the best pose as well as the interactions between the ligand and the residues located at the active site. CONCLUSIONS: The methodology developed for synthesizing the phenylazonaphtol glycosides described proved to be convenient for generating azoic functionalities in the presence of glycosidic bonds and the glycosides suitable as alternative substrates and potentially useful prodrugs in the treatment of colonic diseases.